Analisis Perundungan Berdasarkan Status Gender Dan Orientasi Seksual Di Kalangan Remaja: Implikasi Kesehatan Mental - Novlinda Nurrahma Herman; Fatmah Afrianty Gobel; Fairus Prihatin Idris (Window of Public Health Journal, 2026)
Bullying is an aggressive act carried out repeatedly against individuals perceived as weaker or more vulnerable by individuals or groups with greater power. This study aims to explore in-depth bullying behavior based on gender and sexual orientation among adolescents and its implications for mental health at SMP Negeri 4 Makassar. This research underscores the importance of understanding these dynamics, encouraging educators and professionals to recognize their role in fostering safer environments. The study uses a qualitative, phenomenological approach to understand individual experiences of a particular phenomenon. Through this approach, researchers describe informants' experiences and perceptions regarding bullying behavior. Data collection was conducted through observation and in-depth interviews with 9 informants at SMP Negeri 4 Makassar in March. The results show that the impact of bullying experienced by students at SMP Negeri 4 Makassar is relatively mild, but still has an impact on students' psychological condition and social comfort. The form and dynamics of bullying in adolescents were found to differ by gender, although both boys and girls can act as perpetrators or victims of bullying. In addition, stigma and a lack of understanding regarding sexual orientation also contribute to the occurrence of bullying behavior in the school environment. Based on the research findings, it is recommended that schools increase student education and awareness regarding bullying and provide a more comprehensive understanding of gender and sexual orientation to create a safe, inclusive school environment that supports adolescent mental health.